Значењето на вредностите на прокалцитонинот во рана дијагноза, терапија и прогноза на сепса кај педијатриски пациенти - Нонкуловски, Данило (Медицински факултет, УКИМ, Скопје, 2021)
BACKROUND: Pediatric sepsis is a life-threatening condition induced by micro-organisams, which consists of a range of disorders, when the defensive immune system, instead of controlling the infection, leads to damage to its own tissues and organs. Early diagnosis of sepsis and timely use of antibiotic therapy is essential for life-treatening condition. OBJECTIVE: The aim of this study аre to determine the role of procalcitonin in determining the early diagnosis of sepsis in critical newborn and pediatric haemato-oncology patients with febrile neutropenia. Its sensitivity and specificity in correlation with other inflammatory markers for sepsis (WBC, CRP and blood culture). To determine the prognostic value of procalcitonin as a diagnostic method in critical newborns. In pediatric patients with sepsis, to determine the role of procalcitonin in the choice and duration of antibiotic therapy. METHODS: The study is designed as a prospective, it is being prepared at the PHI University Clinic for Children's Diseases-Skopje. The study involved 160 patients divided into an examination and control group. An examined group of 80 patients aged 0-14 years who will be diagnosed with sepsis according to standard protocols for diagnosis of the disease. 1. subgroup of 50 critical newborns with proven bacterial sepsis at the intensive care and therapy department; 2. subgroup of 30 hаemato-oncology pediatric patients with proven bacterial sepsis with febrile neutropenia. A control group of 80 patients of the same age with infection and signs of inflammation without proven sepsis according to standard protocols for diagnosis of the disease. Procalcitonin will be determined by an immunological method: patented ELFA (Enzyme-linked fluorescent assay) technology, with automated immunological analyzer Vidas Biomerieux (ng / ml). RESULTS: At the first measurement, pediatric patients with sepsis had significantly higher values of procalcitonin compared with pediatric patients without sepsis. The levels of procalcitonin in the blood also determines the severity of sepsis. The diagnostic performance for the validity of procalcitonin in the diagnosis of sepsis in pediatric patients based on the results of the study of procalcitonin was with a sensitivity of 92.5%, specificity 95%, positive predictive value of 94.9% and negative predictive value of 92.7%. According to the values of procalcitonin in the blood in 36% of critical newborns, the antibiotic treatment countinues 21 days, and in the remaining 52% the antibiotic therapy stopped in 14 days. In 26.6% of hаemato-oncology patients with sepsis and febrile neutropenia the antibiotic treatment countinues 21 days, while in the remaining 66.6% the antibiotic therapy stopped in 14 days. CONCLUSION: Procalcitonin is the earliest marker for the diagnosis of sepsis in critical newborns and sepsis in oncologyc patients with febrile neutropenia. Procalcitonin has the highest sensitivity, specificity, positive and negative predictive value in relation to other markers of inflammation and blood culture. Higher levels of procalcitonin in pediatric patient with sepsis are associated with an increased risk of progresion to severe sepsis and septic shock, worsening the prognosis for survival. Dynamics in procalcitonin values have an important role in the choice of antibiotic therapy, its duration, or its modification.
Meaning of the value of procalcitonin in early diagnosis, therapy and prognosis at sepsis in pediatric patients
Докторска дисертација одбранета во 2021 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Ката Мартинова.
Keywords: sepsis, procalcitonin (PCT), pediatric patients